Preparation and Characterization of Strong Cation Exchange Agarose Beads: Influence of Crosslinking and Modeling of Performance Data - Katharina M. Thien; Patrick Adametz; Stella Weber; Florian Taft; Volkmar Thom (Advances in Polymer Technology)
Crosslinking agarose with bisoxiranes and epihalohydrins has been explored for years and is widely applied in the manufacturing of chromatography beads as industrial standard. Nevertheless, the effect on the molecular structure of agarose and the resulting consequences when used as chromatographic adsorber are poorly investigated. Agarose beads modified with 1,4-butanediol diglycidyl ether (BDDE) and epichlorohydrin (ECH), respectively, were characterized regarding their pore size and diffusion coefficients. Modification with BDDE led to reduced pore sizes, whereas no influence could be observed when using ECH. After functionalization as cation exchanger, BDDE- and ECH-modified beads were analyzed among others regarding their binding capacity of lysozyme and γ-globulin. Therefore, the hypothesis of crosslinking-induced diffusion limitation, especially with BDDE, could be further strengthened. Finally, the data were described by calculating the static binding capacity and diffusion coefficient using a cubic grid model and Ogston model, respectively. Overall, those simplified models describe the data quite accurate, whereas the deviation of the model from the static binding capacity is 4% ± 17%, from the diffusion coefficient of the BDDE- or ECH-modified beads 1% ± 16% and from the effective diffusion coefficient of the further sulfonated and column packed beads 11% ± 27%.